Indium-Ill Octreotide Uptake in the Surgical Scar - Degirmenci, B.; Bekis, R.; Sen, M.; Durak, H.; Derebek, E. (Nuklearmedizin - NuclearMedicine, 1999)
Indium-111 octreotide uptake has been reported in various somatostatin receptor positive tumors, granulomas and autoimmune diseases in which activated leucocytes may play a role, subcutaneous cavernous hemangioma and angiofibroma. We present lndium-111 octreotide uptake in a surgical abdominal scar tissue 1.5 and 6 months after surgery in a patient who had been treated for recurrent carcinoid tumor in the rectosigmoid junction, lndium-111 octreotide uptake in a surgical scar may be related to the binding to somatostatin receptors in the activated lymphocytes and fibroblasts that is previously reported.
Keywords: Wound healing; ln-111 octreotide scintigraphy; fibroblasts